Pendampingan Bubble Wrap Exercise Therapy Pada Pasien dengan Distress Diabetes di Wahana Cipta Sinatria Karanganyar - Listrikawati, Martini; Irdianty, Mellia Silvy; Vioneery, Deoni; Fitriyani, Noor (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The prevalence of psychological comorbidities in people with diabetes worldwide is nearly a quarter of people suffer from symptoms of depression or diabetes distress. Management to reduce a person's stress level based on several studies entitled Popping Sealed Air Capsules to Reduce Stress by Dillon KM. The purpose of this service is according to the Bubble Wrap Therapy Training is expected to reduce stress in patients with DM. The method used is a demonstration of bubble wrap exercise training for 15 minutes each part of the feet and hands by pressing bubble wrap using feet and hands and providing health education for 30 minutes on the importance of controlling stress levels in patients with DM. The results of the service show the level of stress with the results of BWET AD ACL from moderate stress level 68.75%, to mild 56.25%. Conclusion Bubble wrap therapy training effectively reduces the level of diabetic distress at Wahana Cipta Sinatria Karanganyar.